Influence of grain size on electromechanical properties of (Ba,Ca)(Zr,Ti)O3: A multiscale analysis using spark plasma sintering and aerosol deposition - Maier, Juliana; Kuhfuß, Michel; Urushihara, Daisuke; Gadelmawla, Ahmed; Khansur, Neamul Hayet; Hall, David; Algueró, Miguel; Martin, Alexander; Kakimoto, Ken ichi; Webber, Kyle Grant (Ceramics International, 2024)
The piezoelectric and ferroelectric properties of aerosol deposited (AD) thick ceramic films are significantly reduced in comparison to bulk materials, which is assumed to be largely related to the nanometer-sized grains (∼0.01 μm) observed in the resulting microstructures. This work, therefore, focuses on understanding the role of grain size in electromechanical properties within the range of AD films based on Ba0.85Ca0.15Zr0.1Ti0.9O3 (BCZT). In a comprehensive compilation of the piezoelectric constant (d33) of samples from various studies the grain size dependency of the d33 was shown for the lead-free ferroelectrics BCZT, BaTiO3, and (K,Na)NbO3. In this, it can be seen that no BCZT sample with a grain size below 0.4 μm was analyzed regarding their d33 before, thereby leaving a gap to the grain size of AD films. In this study, the grain size of ceramic bulk samples was varied using spark plasma and conventional sintering (0.1 μm – 11 μm) and their properties compared to those of AD films. To enable the fabrication of bulk samples in the same range as AD films, a hydrothermal powder with an average particle size of 0.075 μm was synthesized. A continuous increase of the permittivity, the polarization, and the piezoelectric coefficient was observed through grain size increase. These results suggest that the grain size of AD films needs to be enhanced to improve their properties. Importantly, the insights of this multiscale analysis on the grain size can help to tailor also the properties of other BCZT films and bulk samples.
CRIS-Team Scopus Importer:2024-06-14
Keywords: Aerosol deposition; Barium calcium zirconium titanate; Grain size; Lead-free; Spark plasma sintering; Synchrotron